Laser-Induced Periodic Nanostructure on Polyimide Film Surface Using 248 nm Excimer Laser - Songqing Zhao; Xuan Xie; Mingyang Li; Limin Yang; Tongjing Liu (Nanomaterials)
In this study, nanoscale periodic surface structures were fabricated on polyimide (PI) films using a linearly polarized KrF excimer laser with a wavelength of 248 nm. The effects of laser energy density and pulse number on the morphology and surface roughness of laser-induced periodic surface structures (LIPSSs) were systematically investigated. When the pulse width was 20 ns, the repetition rate was 10 Hz, and the beam incidence angle was normal (90°), periodic ripples with a spatial period of approximately 200 nm formed within an energy density range of 7–18 mJ/cm2 and pulse number range of 6000–18,000. The most uniform and well-defined structures were achieved at 14.01 mJ/cm2 and 12,000 pulses, with a ripple depth of 60 nm and surface roughness (<semantics>Ra</semantics>) approximately 26 times greater than that of pristine PI. The ripple orientation was consistently perpendicular to the laser polarization, consistent with low-spatial-frequency LIPSS (LSFL) formation mechanisms governed by interference-induced photothermal effects. In addition, surface wettability was found to be significantly enhanced due to changes in both surface chemistry and topography, with the water contact angle decreasing from 73.7° to 19.7°. These results demonstrate the potential of UV nanosecond laser processing for the scalable fabrication of functional nanostructures on polymer surfaces for applications in surface engineering and biointerfaces.